Hubungan Pengguna Alat Kontrasepsi Suntik dengan Gangguan Mentruasi pada Akseptor KB Suntik 3 Bulan di Klinik Pratama Khoirunnisa Sungai Bahar - Radiah, Radiah; Mansyur, Siti Fatima (Jurnal Akademika Baiturrahim Jambi, 2024)
The practice of using a variety of fertility control methods to help individuals (men and women) or couples have the number and time of children they want to ensure the well-being of both parents is referred to as family planning (KB). Preventing unintended pregnancies with safe methods is the goal of family planning. This is a type of quantitative research that uses an observational analytical research design and a cross-sectional study approach to examine the dynamics of the relationship between the independent variable, which is the use of injectable birth control for three months, and the dependent variable, which is menstrual disorders, simultaneously. Analytical observational research design with a cross-sectional study approach or cross-sectional study to examine the dynamics of the relationship between the independent variable (use of 3-month injectable birth control) and the dependent variable (menstrual disorders) simultaneously is the type of quantitative research used in this study. In January and February of 2023, a number of samples were collected for this study at the Khairunnissa Pratama Clinic in Sungai Bahar Muaro Jambi. Roscoe's theory will be utilized in order to select the study population. where thirty samples were chosen. The information examination technique utilized in this exploration is two phases, specifically Univariate Investigation and Bivariate Investigation. Menstrual disorders are associated with the use of 3-month injections, according to the chisquare test results. The fact that the obtained P value was less than 0.05, or 0.0010.05, when H0 was rejected and H1 was accepted, demonstrates this. With a total of 28 respondents, characteristics based on the type of injectable contraceptive used for three months dominate with a percentage of 100%, and characteristics based on age 18 to 49 years dominate with a total of 30 respondents.